Analisa Performa Bilah Taperless Dengan Airfoil S2091 Pada Turbin Angin Sumbu Horizontal - Irvan Indra Cahyadi; Ratna Dewi Anjani (Jurnal Teknik Mesin, 2021)
Utilization of wind energy is one option to produce electrical energy in the form of wind turbines. Wind energy is also renewable energy that can be utilized because of the potential for wind energy in Indonesia with an average wind speed of 2- 6 m/s. The purpose of this performance analysis is to obtain high efficiency so that the S2091 taperless blade can rotate at relatively low Indonesian wind speeds. Airfoil S2091 has an optimal Cl/Cd value to produce 500 W of power. This performance analysis uses the Blade Element Momentum (BEM) method in which the blade is divided into several elements, starting from determining the radius, chord, and twist on the blade. The assumed parameters will be simulated using Qblade v0.96 software and designing 3D blade designs using SolidWorks software. The dimensions of the taperless blade with the S2091 airfoil have a radius of 0.8 m, a chord of 0.12 m, a twist angle of 6.96o - 9.96o, and a maximum Cp value of 47% at a TSR of 4.5. At a speed of 12 m/s the maximum power generated is 998 W when the angular speed of the blade is 645 rpm and the minimum power generated is 95 W. Then the average power generated is 640.94 W. The results of field tests have a maximum charging power of 138 .46 W and an average charging of 14.13 W. Then the power obtained is 257.80 Wh. From these data, the efficiency of the blade system is 30%–40% and the efficiency of field testing is 34.16%.